A study on observing, detecting, and determining objects in low earth orbit using optical telescope system - Le Xuan, Huy; Nguyen Tien, Su; Trinh Hoang, Quan; Le The, Soat; Trinh Van, Khang; Tran Anh, Tu; La Thuy, Linh (Institute of Advanced Engineering and Science, 2024)
Problems of space debris, space security threats and space accidents are an escalating topic that is drawing attention from scientists and researchers worldwide. Based on the practical demand for detecting and surveilling objects in Earth's orbit in the Vietnam's sky area, the research group has designed a space monitoring system to detect and identify orbiting objects using optical telescopes. The idea of this system is to utilize wide and narrow field-of-view (FOV) optical telescope systems to observe and identify the trajectory of orbiting objects. After an image of an unknown object is captured with a wide FOV telescope, an analyzing algorithm will process and predict the trajectory of it, with support of artificial intelligence, and determine whether there is the appearance of an uncataloged object. If it is affirmative, the narrow telescope system will adapt to a new attitude to track the object from predicted trajectory and gather information for future use. Constructing and validating of this monitoring system deployed by the research group are described in this paper.